Sistem Penguburan di Situs Doro Mpana, Dompu, Nusa Tenggara Barat. - Jamilah, Lila; Srijaya, I Wayan; Agung Bawono, Rochtri (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p12, 2022)
In the Neolithic Period, megalithic cultures emerged that worshiped ancestral spirits, because they were considered to provide welfare and protection to the living. One of the community's activities is the burial of corpses which produces different forms of megalithic buildings. One of the cultural products of the Megalithic tradition is the Doro Mpana site. The excavation findings from 2018 to 2019 were in the form of pottery fragments, ceramic fragments, Dimpa stones, stone artifacts, fragmentary skeletons (skulls, bones and human teeth), and metal objects. The purpose of this study is to understand the burial system and the aspects behind it using religious theory and social stratification theory. Data collection methods consist of observation, interview, literature study, and documentation techniques. Typological, Contextual, Comparative, and Ethnoarcheological analysis methods are also used. The results of this study can reveal the burial system at the Doro Mpana site, namely secondary burial and primary burial carried out in a sitting/folded posture with an orientation (original home of forefather) and a supine position with an orientation (celestial orientation) and accompanied by grave provisions.